A review of the Palaearctic Heliocheilus translucens Felder & Rogenhofer, 1874 species-group with description of a new species from West Mongolia (Lepidoptera, Noctuidae, Heliothinae) - Volynkin, Anton V.; Stüning, Dieter; Matov, Alexej Yu. (Zootaxa, 2015)
Three Palaearctic species of the Heliocheilus translucens species-group are reviewed. One new species, H. tengri Volynkin & Matov, sp. n. is described from West Mongolia, southwestern part of Mongolian Altai Mts. The adults, male and female genitalia are illustrated.